The effectiveness of the procedures in granting halal logo by JAKIM to Malaysian caned food products / Amirah Azhari and Siti Hajar Alias. - Azhari, Amirah; Alias, Siti Hajar (2006)
Recently there has been an increasing demand for halal food in Malaysia markets. This may be due to the increasing number of Muslim population or an increase in their purchasing power. Furthermore, with the advancement of science and technology, it is now possible for various typed of food products to be in the form of canned food products and they are now abundantly available in the supermarkets. These increased in variety of canned food products raised concerned on Muslim consumers with regards to its manufacturing process. The issue is whether these canned food products bearing "halal logo" on their packaging really signifies that the food has been processed according to the actual "halal" process as prescribed by JAKIM in accordance with the Trade Description Act 1972 and The Use of Halal Expression Order 1975. The "halal logo" plays a very important role in certifying the authenticity of JAKIM certification on halal process on the canned food products sold in supermarkets. This is because the Muslim consumers would not be able to access the halal making process of these canned foods are actually complied with except to rely solely on the "halal logo" whenever it appear on the cover of the canned food products. Since there are more than one "halal logo" appearing on the cover of canned food products in Malaysia, it is aims of this research to study how effective is the JAKIM procedures in granting " halal logo" to canned food products. Can these procedures secure that the "halal process" has been observed before the logo was issued either by them of by other authorized body in issuing the "halal logo" to these canned food products. This research will also survey various other "halal logo" available in Malaysian supermarkets.